2014
DOI: 10.1093/nar/gku479
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminus of Mcm10 is important for interaction with the 9-1-1 clamp and in resistance to DNA damage

Abstract: Accurate replication of the genome requires the evolutionarily conserved minichromosome maintenance protein, Mcm10. Although the details of the precise role of Mcm10 in DNA replication are still debated, it interacts with the Mcm2-7 core helicase, the lagging strand polymerase, DNA polymerase-α and the replication clamp, proliferating cell nuclear antigen. Loss of these interactions caused by the depletion of Mcm10 leads to chromosome breakage and cell cycle checkpoint activation. However, whether Mcm10 has an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 51 publications
3
30
0
1
Order By: Relevance
“…1B, left panel). When the same bait vector and yeast strain were used in a previous report by others, a similar extra band was detected by the antiMyc mAb (32).…”
Section: Fpn1 Interacts With Pcbp2 But Not With Pcbp1 Pcbp3 or Pcbpsupporting
confidence: 68%
See 1 more Smart Citation
“…1B, left panel). When the same bait vector and yeast strain were used in a previous report by others, a similar extra band was detected by the antiMyc mAb (32).…”
Section: Fpn1 Interacts With Pcbp2 But Not With Pcbp1 Pcbp3 or Pcbpsupporting
confidence: 68%
“…Considering this finding, two other sources of anti-HA mAbs (from Wako Chemicals (Osaka Japan) and Covance Laboratories (Madison, WI)) were utilized for detection, and again, a similar pattern of multiple bands was detected (data not shown). Of interest, when the same prey vector and yeast strain were used in previous reports by others, similar multiple bands were detected by the anti-HA mAb (32,33).…”
Section: Fpn1 Interacts With Pcbp2 But Not With Pcbp1 Pcbp3 or Pcbpsupporting
confidence: 67%
“…Alver et al 33 . have shown that N-terminus of Mcm10 plays an important role in resisting the DNA damage induced by different genomic insults including treatment with camptothecin in budding yeast.…”
Section: Resultsmentioning
confidence: 99%
“…All transgenes were expressed from a plasmid that contained the endogenous MCM10 promoter [17]. Plasmids expressing wild-type or mutant MCM10 were transformed into the mcm10-1 strain and spotted on SC-URA plates in 10-fold dilutions.…”
Section: Resultsmentioning
confidence: 99%